Math Anxiety among Secondary School Students: Causes and Consequences in Azerbaijani Schools - Gasimova, Jahan (ADA University, 2025)
This study investigates the causes and consequences of math anxiety among lower secondary students (grades 5, 6, and 7) in Azerbaijan, with a particular focus on its cognitive, emotional, and environmental dimensions. Utilizing a mixed-methods research design, the study draws on the data collected from sixty student surveys and semi-structured interviews with six mathematics teachers across two schools in Baku, Azerbaijan. The research addresses three questions: What cognitive, environmental and social factors contribute to math anxiety? What are perceived influences of math anxiety on students’ academic performance in mathematics? Are there any gender differences in students’ experiences of math anxiety? Findings of this study reveal that math anxiety is a prevalent and multifaceted phenomenon. Surveyed students commonly reported anxiety during high-stakes evaluations, often triggered by fear of mistakes, high parental expectations, and peer judgment. The teacher interviews supported these findings, highlighting emotional disengagement, avoidance behaviors, and cognitive overload as recurring issues. The study also found a negative correlation between math anxiety and performance; gender differences emerged as well, where female students were more likely to experience and internalize anxiety and exhibit emotional responses, while male students tended to mask their anxiety or disengage silently. This research contributes local empirical evidence to the literature on math anxiety and underscores the need for targeted interventions. Recommendations include fostering a supportive classroom environment, promoting growth mindsets, and engaging parents in constructive dialogues. The study concludes with suggestions for further research, including further longitudinal and intervention-based studies to explore causality and effective strategies for reducing math anxiety.
Keywords: Mathematics anxiety -- Study and teaching -- Azerbaijan.; Academic achievement -- Psychological aspects.; Middle school students -- Psychology.; Educational psychology.; Gender differences -- Educational aspects.; Family support -- Educational aspects.